COMBINATION OF DIRECT RENNIN INHIBITOR - ALISKIREN, ANGIOTENSIN II RECEPTOR BLOCKER - VALSARTAN, AND CALCIUM CHANNEL BLOCKER - AMLODIPINE, IN THERAPY OF HYPERTENSIVE PATIENT WITH GOUT (CASE REPORT) - O. V. Dralova; M. L. Maksimov (Рациональная фармакотерапия в кардиологии)
Pharmacotherapy optimization in patients with arterial hypertension and gout is very important. Achievement of the target blood pressure levels is possible with the use of combinations of effective antihypertensive drugs with neutral metabolic profile and safety, in particular a combination of valsartan, amlodipine and aliskiren. Clinical case of this combination use in patient with arterial hypertension and gout is presented.